Intelligent wound dressing for diagnostic & therapeutic applications - critical to wound infection. Issue 7 (10th July 2020) - Mahmood, Zahid; Salisbury, Anne-Marie; Chen, Rui; Rimmer, Stephen; Percival, Steven
Abstract : A medical device comprising of biomaterials responsive to biochemical stimuli: channel for indicating the infective states of wounds and ensuring delivery of smart antimicrobial and antibiofilm agents to promote tissue regeneration and healing. The importance of providing diagnostic wound dressings that can inform healthcare professionals on the state of infection within wounds but also provide some of the treatment required in response to at risk or infected wounds is of key interest. The aim is to investigate an innovative proof of concept diagnostic and detection system, an intelligent hydrogel wound dressing that responds to specific biochemical stimuli in wounds (MMPs and pH) enabling the selective and triggered release of antibiofilm and antimicrobial agents ('Detect and Treat')to the trauma site. The dressing is made of a sterile alginate core material covered in a biocompatible dry or hydrated peptide-polymer-complex film and may include a fluorescent dye which upon release during the wound healing process indicates when a change in dressing is necessary. Efficacy studies of the hydrogel dressing were performed within a drip-flow bioreactor in which regression of Pseudomonas aeruginosa biofilm was observed. A 5-log reduction in biofilm was observed in comparison to an untreated control biofilm. The hydrogel dressing indicated a clear response when in contact with biofilms produced only by pathogenic strains of bacteria when analysed. This further confirmed the adequate release and function of the antimicrobial and antibiofilm agents within the peptide-polymer-complex formulation of the hydrogel wound dressing.